2009
DOI: 10.1038/ng.481
|View full text |Cite
|
Sign up to set email alerts
|

A small recurrent deletion within 15q13.3 is associated with a range of neurodevelopmental phenotypes

Abstract: We report a recurrent 680-kb deletion within chromosome 15q13.3 in ten individuals, from four unrelated families, with neurodevelopmental phenotypes including developmental delay, mental retardation and seizures. This deletion likely resulted from nonallelic homologous recombination between low-copy repeats on the normal and inverted region of chromosome 15q13.3. Although this deletion also affects OTUD7A, accumulated data suggest that haploinsufficiency of CHRNA7 is causative for the majority of neurodevelopm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
180
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 15 publications
8
180
1
Order By: Relevance
“…[25][26][27][28] These B2-Mb microdeletions lead to the loss of CHRNA7 and five other genes (Supplementary Figure 1a), but smaller variants that show a similar range of phenotypes remove only CHRNA7 and one other gene. 29 These observations strongly implicate the CHRNA7 region in schizophrenia and other neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 93%
“…[25][26][27][28] These B2-Mb microdeletions lead to the loss of CHRNA7 and five other genes (Supplementary Figure 1a), but smaller variants that show a similar range of phenotypes remove only CHRNA7 and one other gene. 29 These observations strongly implicate the CHRNA7 region in schizophrenia and other neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8] The phenotype varies in spectrum and severity owing to incomplete penetrance or variable expressivity. The 15q13.3 deletion is typically 1.6 Mb, harboring at least seven genes, ARHGAP11B, MTMR15, MTMR10, TRPM1, KLF13, OTUD7A, and CHRNA7.…”
Section: Introductionmentioning
confidence: 99%
“…This subunit has important roles in brain development and neuron differentiation and migration (Gotti et al 2009;Taly et al 2009), and its chromosomal locus was associated in humans with developmental and neurological disorders (Ben-Shachar et al 2009;Consortium 2008;Helbig et al 2009;Miller et al 2009;Sharp et al 2008;Shinawi et al 2009;Stefansson et al 2008). Despite the importance of the α7 nAChR subunit, its deficiency results in viable, anatomically normal α7-null mice (Orr-Urtreger et al 1997;Paylor et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The nAChRs have been implicated in complex diseases affecting the nervous system, including epilepsy, schizophrenia, developmental disorders, and aging-associated neurodegenerative diseases such as AD and PD (Freedman et al 2001;Steinlein et al 1995). Several recent genome-wide association studies identified genomic alterations in the human α7 nAChR subunit gene locus in patients with schizophrenia, bipolar disorder, autism, developmental delay, and seizures (Ben-Shachar et al 2009;Consortium 2008;Helbig et al 2009;Miller et al 2009;Sharp et al 2008;Shinawi et al 2009;Stefansson et al 2008). α7 subunits can form homopentameric receptor channels, which are activated by acetylcholine (ACh) and blocked by α-bungarotoxin (αBgtx).…”
Section: Introductionmentioning
confidence: 99%